Synthesis and characteristics of nanostructured silicon-rich nitride thin films using modified long-wavelength CO2 laser annealing. (25th August 2015) - Chung, C K; Li, C H; Chen, T S
Abstract: The silicon nanocrystals (nc-Si) or nanoparticles (np-Si) surrounded by a dielectric matrix of SiN x or SiO x were traditionally synthesized by chemical vapor deposition and subsequent furnace annealing at a high temperature of 1000 °C on the whole wafer. The short-wavelength (248 nm) KrF excimer laser could also be used for assisting annealing. In this article, the unique method of glass assisted long-wavelength (10.6 μ m) CO2 laser annealing through local heating was applied to produce crystallized np-Si on sputtered silicon-rich nitride (SRN) thin films. Various CO2 laser fluences were irradiated on SRN films for studying the evolution of the microstructure and optoelectronic characteristics of films. The size of np-Si on SRN films increases with the laser fluence. According to the photoluminescence (PL) and bonding configuration results, two broad-visible PL spectra of the films were deconvoluted into three bands within wavelengths of 350~650 nm linked to the unsatisfied interface states, the located states related to the mixed Si–O or Si–N bonds in the SRN layer, and the nc-Si embedded in an a-SiO x N y matrix, respectively. The relationship between the laser fluence, microstructure, and PL behavior of SRN films was discussed and established.